Pediatric bronchogenic cysts in the head and neck region: A study of 10 surgical cases and a review of the literature - Chen, Wei; Xu, MengRou; Wang, Qingyu; Xu, Hongming; Chen, Jiarui; Li, Xiaoyan (Frontiers in Pediatrics, 2022)
Objective To explore the clinical characteristics and surgical treatment of children with bronchogenic cysts (BCs) in the head and neck region. Methods A retrospective study of 10 pediatric patients with BCs in the head and neck region treated in Shanghai Children's Hospital during 2011 to 2022 was performed. Results Based on their pathological diagnosis, 10 patients with BCs in the head and neck were identified. The most common location was the neck (8 patients, 80%; 2 midline neck, 6 lateral neck), followed by the ventral tip of tongue (1 patient), and the posterior pharyngeal wall (1 patient). Misdiagnosed as lymphangioma in 5 cases, cyst in 3 cases, thyroglossal duct cyst (TGDC) in 2 cases and congenital pyriform sinus fistula (CPSF) in 1 case preoperative. The median follow-up period after surgery was 4.68 (range, 0.67–9.25) years. All 10 patients underwent complete resection without recurrence or other complications. Conclusions Although extremely rare, BCs should be considered in the differential diagnosis of midline and lateral neck masses or intraoral cysts in children. Surgical excision is recommended in BCs, and the diagnosis is definitively confirmed by histopathology.